2010
DOI: 10.1080/19361521003761416
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support for Israeli Adolescents Continually Exposed to Terrorism: Protective or Compensatory Factors?

Abstract: This study investigated the role that social support plays in posttraumatic stress (PTS) and depressive symptoms among Israeli adolescents with high or low exposure to terrorist acts. Participants were 585 Jewish students (221 girls and 364 boys) in grades 7 to 12 from areas extensively versus slightly exposed to terrorist attacks. Results found that PTS levels and depressive symptoms were higher among adolescents residing in areas highly exposed to terrorism. Adolescents in high exposure areas reported lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In this study both social support and religiosity moderated the negative effect of social adversity on SVR. In the literature social support has been shown to be a central, yet complex, factor interacting with SVR [54], and our results confirm that social support buffers the link between social adversity and SVR in a sample of both majority and minority students.…”
Section: Discussionsupporting
confidence: 83%
“…In this study both social support and religiosity moderated the negative effect of social adversity on SVR. In the literature social support has been shown to be a central, yet complex, factor interacting with SVR [54], and our results confirm that social support buffers the link between social adversity and SVR in a sample of both majority and minority students.…”
Section: Discussionsupporting
confidence: 83%
“…This fear may also lead individuals into a state of physical and psychological resource loss or strain, which lowers their well-being [ 30 , 33 ]. Other studies have also led to similar findings that a loss of resources is positively related to psychological strain in adolescents [ 34 , 35 ]. Similarly, Reade and Lee [ 36 ] found that individual exposure to ethnopolitical conflict resulted in psychological resource loss.…”
Section: Literature Reviewsupporting
confidence: 53%
“…In studies on trait resilience and similar concepts (e.g., hardiness) as well as social support ( Cohen and Wills, 1985 ; Beasley et al, 2003 ; Schiff et al, 2010 ; Kaniasty et al, 2020 ) an important question that researchers have been asking themselves is: are these factors having direct effects on wellbeing, independently of the levels of exposition to risks and adverse situations, or do they have interactive, buffering effects specifically associated with reduced impacts of stressors and adverse situations on wellbeing and mental health? As indicated above, all of the five considered potential resilience factors emerged as having positive main relationships on at least one of the wellbeing outcomes constructs, providing support to a direct effect model of protective influence.…”
Section: Discussionmentioning
confidence: 99%